Industrial controlling process using the remote industrial automation trainer PAIR - Silva, M. (2015)
This paper describes the development of the PAIR (Remote Industrial Automation Trainer) platform, an open access tool, to assist learning of industrial process automation. The students can practice their theoretical knowledge by exploring automation concepts based on some real world scenarios.. An experiment is used to better explain PAIR design.